An Investigation of Executive Functioning in Pediatric Anxiety. Issue 6 (November 2018) - Murphy, Yolanda E.; Luke, Anna; Brennan, Elle; Francazio, Sarah; Christopher, Isabella; Flessner, Christopher A.
Although science's understanding (e.g., etiology, maintaining factors, etc.) of pediatric anxiety and related problems has grown substantially over recent years, several aspects to anxiety in youths remain elusive, particularly with relation to executive functioning. To this end, the current study sought to examine several facets to executive functioning (i.e., cognitive flexibility, inhibition, planning, working memory) within a transdiagnostic sample of youths exhibiting varying degrees of anxiety symptoms. One hundred six youths completed a comprehensive battery, including several self-report measures (e.g., Multidimensional Anxiety Scale for Children [MASC] or MASC-2) and an automated neurocognitive battery of several executive functioning tasks (Intradimensional/Extradimensional [IDED], Stop Signal [SST], Spatial Span [SSP], Stockings of Cambridge [SOC] tasks). Regression analyses indicated that youths exhibiting marked anxiety symptoms demonstrated increased planning time and probability of inhibition compared with youths with minimal or no anxiety symptoms. Youths with marked anxiety symptoms similarly demonstrated better cognitive flexibility (i.e., set shifting) compared with youths with minimal anxiety. In addition, analyses indicated a trend such that youths exhibiting marked anxiety symptoms demonstrated poorer working memory compared with youths with no anxiety symptoms. Group classification did not predict remaining outcomes. Limitations and future areas of research are discussed.